Observation of antitumor mechanism of GE11-modified paclitaxel and curcumin liposomes based on cellular morphology changes - Hailing Tang; Lijuan Li; Baoshan Wang; Guangxi Scientific Research Center of Traditional Chinese Medicine (SpringerOpen, 2024)
Abstract Curcumin and paclitaxel are widely used as anti-tumor hydrophobic model drugs for the designation of smart tumor-targeting nanocarriers and the study of the correlation between structural characteristics of nanoparticles and in vivo therapeutic efficacy. Various signaling pathways on cell growth and proliferation have been comprehensively studied in vitro and in vivo under the action of curcumin and paclitaxel nanoparticles. In this paper, we prepared EGFR-targeted GE11 peptide-modified curcumin and paclitaxel compound liposomes (CUR-PTX@GE11-L). The tumor suppression mechanism of CUR-PTX@GE11-L is observed from the aspects of drug release behavior, changes of cell morphology, liver retention, and tumor-targeting efficiency. We hope it can provide a new vision for the rational construction of smart nanoscale drug delivery system through the observation of cytotoxic effects of CUR-PTX@GE11-L, especially on the cellular morphology change. Graphical Abstract